Gestión de continuidad en el área de pasantías del programa de administración de negocios de la universidad del Quindío para la concertación de convenios interinstitucionales de cooperación con empresas del sector servicios de la ciudad de Armenia. (2015)
The Program of Business Administration of the University of the Quindío form leading qualified and committed professionals; capable of responding to the social and organizational challenges in a globalized world, where decision-making is important to resolve any business drawback. This is where the new economic dynamism in which business organizations are immersed in the world today, it requires continuous competitive strategies to stay in a globalized market, full of uncertainty and instability so they will have to re fit both internally and externally. Taking into account that at present the economy develops under the phenomenon of globalization, an analysis of the service sector at the global, national and local levels will be presented to identify: as has been its development, current situation, advantages and problems that the sector has been presented throughout its development and what are the projections for the future in these scenarios. In the development of the present investigation it will be demonstrated a study of diagnostic investigation to identify the companies MSMES that are part of the services sector of the city of Armenia and with which you can perform the approach with the program of business administration, In the same way we will know the strategies to make new inter-agency agreements of cooperation with companies in the sector, and finally to promote efficiently the internship program’s area mentioned above.